2020
DOI: 10.3390/ijerph17082900
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Factors and Psychological Factors Associated with Elevated Psychological Distress among Dentists and Dental Hygienists in Israel

Abstract: The aim of this study was to evaluate the association of COVID-19 factors and psychological factors with psychological distress among dental staff during the COVID-19 pandemic outbreak. A cross-sectional survey was conducted among 338 Israeli dentists and dental hygienists, who provided their demographic data; answered questions about COVID-19-related factors; and were assessed by subjective overload, self-efficacy, and psychological distress scales. Data were analyzed using a multivariate logistic regression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
335
4
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 282 publications
(392 citation statements)
references
References 33 publications
33
335
4
20
Order By: Relevance
“…Being in a committed relationship: This was found to be protective by Shacham et al [34] This was not directly assessed in other studies. Safety of family: This had the biggest impact in reducing stress in a cross-sectional study by H. Cai et al [23] This was also not assessed in other studies.…”
Section: Occupational Factorsmentioning
confidence: 88%
See 4 more Smart Citations
“…Being in a committed relationship: This was found to be protective by Shacham et al [34] This was not directly assessed in other studies. Safety of family: This had the biggest impact in reducing stress in a cross-sectional study by H. Cai et al [23] This was also not assessed in other studies.…”
Section: Occupational Factorsmentioning
confidence: 88%
“…A study of dentists in Israel found an increase in psychological distress in those with background illnesses as well as an increased fear of contracting COVID-19 and higher subjective overload. [34] In medical HCWs in China, organic illness was found to be an independent risk factor for insomnia, anxiety, OCD, somatising symptoms and depression in medical HCWs. [43] There was also a signi cant association between physical symptoms and poor psychological outcomes in a large multicentre study based in India and Singapore.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
See 3 more Smart Citations